The Early Wisconsinan History of the Laurentide Ice Sheet - Vincent, Jean-Serge; Prest, Victor (Géographie physique et Quaternaire, 1987)
ABSTRACTThe identification, particularly at the periphery of the ice sheet, of glacigenic sediments thought to postdate nonglacial sediments or paleosols regarded as having been laid down sometime during the Sangamonian Interglaciation (stage 5) and thought to predate nonglacial sediments or soils reckoned to be of Middle Wisconsinan age (stage 3), has led numerous authors to propose that the Laurentide Ice Sheet initially grew during the Sangamonian and/or the Early Wisconsinan (stage 4). The evidence for the beginning of the Wisconsinan ice sheet in various areas of Canada and the northern United States is briefly reviewed. The general absence of sound geochronometric frameworks for potential Sangamonian or Early Wisconsinan glacial deposits has led to a situation where in most areas it can be argued, depending on one's interpretation, that ice completely inundated or was completely absent at that time. On the premise (perhaps false) that Laurentide Ice was in fact extensive during the Early Wisconsinan, a map showing maximum possible ice extent, as put forward by some authors is presented and the glacigenic units possibly recording the ice advance are shown in a correlation chart. This post Sangamonian sensu stricto (substage 5e) -pre Middle Wisconsinan limit of ice extent is generally more extensive than the Late Wisconsinan (stage 2) limit. The geometry of the ice sheet margin and scanty available information on direction of ice movements indicate that this assumed Early Wisconsinan ice likely developed in a very similar manner to that of the Late Wisconsinan ice complex. A hypothetical growth model of the Laurentide Ice Sheet, following the last interglaciation is also proposed.